2003
DOI: 10.3318/bioe.2003.103.3.187
|View full text |Cite
|
Sign up to set email alerts
|

Physico–Chemical Characteristics and macroinvertebrate Communities of the Caher River

Abstract: A study of the physico-chemical characteristics of the Caher River, Co. Clare, was carried out at two sites between October 1999 and April 2000. The Caher is an alkaline system with pH values in excess of 8.0. Phosphate and nitrogen concentrations showed no evidence of eutrophication. Conductivity values were at the lower end of the range expected for a limestone region. Calcium concentrations were relatively high, and precipitation of calcium carbonate was evident for much of the lower course of the river. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Tavzes et al (2006) reported H. stagnalis from the moderately polluted sites of urbanized small Glinščica stream, and Bubinas and Jagminienë (2002) found this species from slightly polluted Neris River. Kelly-Quinn et al (2003) also found H. stagnalis in Caher River with high water quality and high ecological status. Agapow et al (2006) recorded this species from Lubiatowskie Lakes in Poland with moderate and low water quality.…”
Section: Resultsmentioning
confidence: 99%
“…Tavzes et al (2006) reported H. stagnalis from the moderately polluted sites of urbanized small Glinščica stream, and Bubinas and Jagminienë (2002) found this species from slightly polluted Neris River. Kelly-Quinn et al (2003) also found H. stagnalis in Caher River with high water quality and high ecological status. Agapow et al (2006) recorded this species from Lubiatowskie Lakes in Poland with moderate and low water quality.…”
Section: Resultsmentioning
confidence: 99%
“…and Psammoryctides spp.-see Table II) indicated poor water quality of the lake (characterized by low dissolved oxygen and high nutrient concentrations). Although, dissolved oxygen levels of the lake not low but high value of some Ammonium ions might be limiting for many species, these conditions favoured Potamothrix, Limnodrilus, some Gastropods and Chironomids [30]- [31] …”
Section: Biological Resultsmentioning
confidence: 99%